People’s Behavior in Decision Making in elect Members of the House of Representatives’s B.E. 2562 in Khon Kaen Province Constituency 2 - Choutikavatchagul, Songphon; Promgun, Suraphon; Namseethan, Somkhuan (Journal of Modern Learning Development, 2021)
The objectives of this research were: 1) to study the level of people's behavior in decision-making to exercise their right to vote for members of the House of Representatives 2019 in Khon Kaen Province 2nd Constituency; 2) to compare the behaviors of the people according to their personal factors; 3) to study relationship between social factors and people's behavior in decision-making to exercise the right to vote for the aforesaid members; 4) to study the recommendations of people's behavior in decision-making to vote for the members of the House of Representatives. The sample group used in the study consisted of 399 people and 8 key informants. The tools used were questionnaires and interview forms. The statistics used to analyze the data were: Frequency, Percentage, Standard Deviation, and Chi-Square Statistics. For the qualitative research, the data were analyzed using contextual content analysis techniques. The research results were as follows: 1) The level of people's behavior in deciding to exercise the right to vote for members of the House of Representatives 2019 in Khon Kaen Province Constituency 2 as a whole was at a high level. 2) Comparison results of people's gender, age, education level, occupation, monthly income revealed that their behavior in decision-making to exercise their right to vote for members of the House of Representatives 2019 in Khon Kaen Province, 2nd constituency was indifferent. This is not in accordance with the hypothesis set. 3) The relationship between social factors and people's behavior in deciding to exercise their right to vote for members of the House of Representatives 2019 in Khon Kaen Province, 2nd Constituency 2, had a statistically significant relationship at the 0.05 level. 4) Recommendations on people's behavior in deciding to exercise the right to vote for members of the House of Representatives are to create interest and enthusiasm for voters by the way that the candidates must develop the country in accordance with the policies previously provided; candidates must be competent and work on-site to support the people as they have promised; candidates must have a vision that will lead the people to gain well-being and safe in society.